Comparison of heel stick sample with placental blood sample for pretransfusion testing. Issue 9 (28th August 2018) - Aysola, Agnes E.; Duque, Miriam Andrea; Williams, Patty; Alissa, Rana
Abstract : BACKGROUND: Published studies demonstrate that placental blood samples provide acceptable results for various laboratory tests, but these studies did not include pretransfusion testing. The aim of this study was to show concordance between heel stick and placental blood sample pairs for pretransfusion testing and to validate tube and gel method for placental samples. Using placental blood samples for pretransfusion testing potentially reduces the amount of blood collected from newborns for initial laboratory tests. STUDY DESIGN AND METHODS: Placental samples were collected for pretransfusion tests at birth from 32 newborns with less than 2000 g birthweight and less than 35 weeks to compare the results with the heel stick samples from the same newborns. ABO and D typing, direct antiglobulin test (DAT) with IgG, and antibody screen tests were performed on these sample pairs. For ABO and D typing both tube and gel methods were used to validate both methods for the placental samples. RESULTS: This study shows 100% concordance in 32 sample pairs for ABO, D, and DAT tests. Antibody screen results were compared on 29 sample pairs. All 28 sample pairs were concordant, but one placental blood sample was more sensitive to detect a weak maternal antibody than its corresponding heel stick sample was. CONCLUSION: The results of this study validated that placental blood samples can be used in place of heel stick samples and are suitable for pretransfusion testing. This study also validated ABO and D typing by tube and gel methods for placental samples.